Accelerating particle-resolved CFD simulations of catalytic fixed-bed reactors with DUO. (15th March 2022) - Daymo, Eric A.; Hettel, Matthias; Deutschmann, Olaf; Wehinger, Gregor D.
Graphical abstract: Highlights: 3D modeling of an 86-particle fixed bed with CPOX and DRM chemistry. ISAT and CA methods used to accelerate the calculation of reaction source terms. CA method is simpler than other implementations of this acceleration technique. ISAT and CA methods were added to DUO, which couples OpenFOAM and DETCHEM. Speedup factors were 7x for CPOX and 35x for DRM, with acceptable calculation errors. Abstract: Simulation of fixed-bed catalytic reactors is important for engineering industrial technologies. The large number of catalytically active surface faces makes the application of microkinetic models too time consuming for large 3D simulations that include fully resolved particle structures (e.g., ≫ 10′s of particles). Such simulations, though, are often required for small tube-to-particle diameter ratio configurations, where local flow effects are difficult to capture with 1D or 2D simulations. A common solution for speeding up reactive computational fluid dynamics (CFD) involves the use of chemistry acceleration methods, including In-Situ Adaptive Tabulation (ISAT) and Cell Agglomeration (CA). In the present contribution, DUO (DETCHEM TM + OpenFOAM coupling) CFD software has been extended to include ISAT and CA methods for surface reactions, in particular, using a CA method that is simpler than other implementations of this acceleration technique. Speedup factors and errors were tabulated for an 86 spherical particle 3D resolved fixed-bed reactor, considering the exothermic methane catalytic partial oxidation (CPOX) and the endothermic dry reforming of methane (DRM) chemistries. For CPOX, a speedup factor of ∼ 7x was achieved, while for DRM, a speedup of ∼ 35x was obtained, with both cases achieving an acceptable error in the solution. Although a tighter error tolerance with ISAT and CA is shown to reduce the overall calculation error, for some engineering situations this tradeoff in speedup and accuracy will be acceptable. Achieving usable results in around 0.5 – 2 h instead of around 20-hours (for these chemistries on this particular grid, run on a 400-core cluster) can vastly improve the feasibility of computational fluid dynamics for the analysis of fixed-bed catalytic reactors including microkinetics mechanisms.